Synergistic Enhancement of the Lubrication Performance of Zinc Dialkyldithiophosphate by Coexistence with Ionic Liquid - Kaisei Sato (Japanese Society of Tribologists, 2021)
Ionic liquids (ILs) are being considered as novel lubricant additives to improve the friction and anti-wear characteristics of sliding surfaces. Because ILs consist of only cations and anions, their physical and chemical properties can be easily tailored by modifying their combination. These features enable to design of specific ILs for a given tribological system. However, there are few reports on the effect of ILs used as lubricant additives on the friction and anti-wear characteristics of sliding surfaces. Moreover, it is necessary to investigate the synergism between ILs and other lubricant additives to achieve high practical efficiency. Therefore, in this study, two ILs with different cations but similar anions were used in combination with an anti-wear additive, zinc dialkyldithiophosphate (ZDDP), and the resultant wear and friction characteristics of the worn surfaces were analyzed. We found that the tribological performance under steel/steel sliding conditions was dependent on the chemical composition of the ILs. In addition, mixed ZDDP and IL solutions exhibited lower friction and wear when compared to ZDDP alone. It is considered that the excellent lubrication and frictional performance observed with the mixed lubricant solutions is due to the formation of tribofilms comprising of ZDDP and IL on the sliding surface.